GAMBARAN STATUS GIZI PADA SISWA SEKOLAH DASAR KECAMATAN BANGKO KABUPATEN ROKAN HILIR - Lestari, Indah Dian; Ernalia, Yanti; Restuastuti, Tuti (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2016)
ABSTRACTPrimary school students are the group of student that potentially having problem with nutrition due to their eating behavior and development status. Good nutritional status will affect the growth and development of children, one of which can increase the intellectual capability. This study aimed to determine the overview of nutritional status of children in elementary school on district Bangko Rokan Hilir regency. This research is a descriptive study. The subject in this research were 210 students from grade 1 – 6 were taken with cluster sampling technique. Each of the subject asked to bring questionnaires to the parent to get the characteristic data of the student and then calculated children BMI by measuring height and weight. Nutritional status is divided into very thin, thin, normal, obese and very obese, based on anthropometric indices with BIM per age. The data showed that children with malnutrition were 50 children (23,8%), underweight were 58 children (27,6%), normal were 93 children (44,3%), overweight were 7 children (3,3%), and obesity were 2 children (1,0%).Keywords : children of school age, nutrition, nutritional status